MENINGKATKAN KEMAMPUAN BERBICARA ANAK USIA 5-6 TAHUN MELALUI MENONTON VCD CERITA ANAK - Nurbiana Dhieni; Sri Indah Pujiastuti; Aryanti Aryanti (Perspektif Ilmu Pendidikan, 2010)
The purpose of this research is to develop the speaking ability of 5-6 years’ children at the Kindergarten of Islam Al-Fattah in Wanasari Village, Bekasi District by watching video. The research applied classroom action research within two cycles. Each cycles consisted of planning, action, observation, and reflection. The subjects of the research included ten children of B group who have speaking ability problems. The data were collected using no-test instruments such as observation, interview, and document study. The data were analyzed employing qualitative and quantitative paradigm. The result of the research show that using video can improve the children speaking ability.